Methodology for the evaluation of the Stephanie Alexander Kitchen Garden program. (27th March 2013) - Gibbs, L.; Staiger, P. K.; Townsend, M.; Macfarlane, S.; Gold, L.; Block, K.; Johnson, B.; Kulas, J.; Waters, E.
Abstract : Issues addressed: Community and school cooking and gardening programs have recently increased internationally. However, despite promising indications, there is limited evidence of their effectiveness. This paper presents the evaluation framework and methods negotiated and developed to meet the information needs of all stakeholders for the Stephanie Alexander Kitchen Garden (SAKG) program, a combined cooking and gardening program implemented in selectively funded primary schools across Australia. Methods: The evaluation used multiple aligned theoretical frameworks and models, including a public health ecological approach, principles of effective health promotion and models of experiential learning. The evaluation is a non‐randomised comparison of six schools receiving the program (intervention) and six comparison schools (all government‐funded primary schools) in urban and rural areas of Victoria, Australia. A mixed‐methods approach was used, relying on qualitative measures to understand changes in school cultures and the experiential impacts on children, families, teachers, parents and volunteers, and quantitative measures at baseline and 1 year follow up to provide supporting information regarding patterns of change. Results: The evaluation study design addressed the limitations of many existing evaluation studies of cooking or garden programs. The multistrand approach to the mixed methodology maintained the rigour of the respective methods and provided an opportunity to explore complexity in the findings. Limited sensitivity of some of the quantitative measures was identified, as well as the potential for bias in the coding of the open‐ended questions. Conclusion: The SAKG evaluation methodology will address the need for appropriate evaluation approaches for school‐based kitchen garden programs. It demonstrates the feasibility of a meaningful, comprehensive evaluation of school‐based programs and also demonstrates the central role qualitative methods can have in a mixed‐method evaluation. So what?: This paper contributes to debate about appropriate evaluation approaches to meet the information needs of all stakeholders and will support the sharing of measures and potential comparisons between program outcomes for comparable population groups and settings. Abstract : This paper presents the evaluation framework and methods for the Stephanie Alexander Kitchen Garden program, a combined cooking and gardening program implemented in selectively funded primary schools across Australia. The usefulness of the study design and the respective methods are discussed. In doing so, the paper contributes to debate about appropriate and feasible evaluation approaches to meet the information needs of all stakeholders.